A Effects of exogenous shocks on Africa's participation in world trade: empirical evidence from the Franc zone. - nitedem kenney, prudence nicaise; ONGO NKOA, Bruno Emmanuel (Quantitative Economics and Management Studies, 2025)
This study examines the influence of external disturbances - such as world energy and oil costs, key interest rates and the money supply of major economic powers (Federal Reserve Bank (FED), People's Bank of China) on the engagement of French-speaking countries in world trade. We developed a composite index of external shocks using principal component analysis (PCA), with the aim of reflecting the shared dynamics of these variables. A Panel VAR (PVAR) model was estimated based on quarterly data from 2000 to 2018. The data show that these disruptions have a significant and time-varying impact on franc zone trade, underlining strong external dependence. The study recommends a better alignment of economic policies, dynamic cyclical surveillance and a policy of diversifying trading partners in order to consolidate the resilience of Franc zone economies to international disruptions.